Changes in Mechanisms and Characteristics of Western U.S. Floods Over the Last Sixty Years. Issue 3 (9th February 2022) - Huang, Huilin; Fischella, Michael R.; Liu, Yufei; Ban, Zhaoxin; Fayne, Jessica V.; Li, Dongyue; Cavanaugh, Kyle C.; Lettenmaier, Dennis P.
Abstract: Climate change is linked to changing precipitation, yet uncertainty remains as to whether and how hydroclimatic changes will influence flood frequency, magnitude, and timing. Part of this uncertainty is because few regional‐scale studies have analyzed changes in floods produced by different mechanisms. We identify six flood generating mechanisms (FGMs) based on prominent meteorological processes and moisture supply to the soil column in the Western U.S.; these include large‐scale frontal storms (atmospheric and non‐atmospheric rivers), monsoons, convective storms, snowmelt, and rain‐on‐snow. We assess trends in the frequency, magnitude, and timing of floods produced by different FGMs across 119 basins during 1960–2018. Overall, we find decreased frequency and magnitude of rain‐on‐snow‐driven floods, increased frequency and magnitude of convective‐storm‐driven floods, and a temporal shift to earlier in the year for snowmelt‐driven floods. The flood characteristics are generally stable for floods produced by other FGMs. Plain Language Summary: Floods are among the most common and costliest of natural disasters. Extreme rainfall is a major cause of flooding and has become more common as global temperatures have increased. However, many studies show that the number and size of flood events remain mostly unchanged. It is possible that climate change is affecting different types of floods in different ways, and so we separate floods into different categories and evaluate trends on a category‐by‐category basis. In particular, we group floods across the western U.S. into six categories, which we term flood generating mechanisms (FGMs). These include rain‐on‐snow, snowmelt, monsoons, convective storms, and two types of frontal storms. We then separately describe trends in the frequency, magnitude, and timing for each FGM from 1960 to 2018. We find that floods generated by convective storms have become more common and more extreme. On the other hand, rain‐on‐snow floods have become rarer and less extreme. Also, floods caused by snowmelt are occurring earlier within the year. Most of the other categories do not show significant changes in flood characteristics. These results give us important information on the types of flooding that may be most impacted by future climate change, which can aid future flood planning efforts. Key Points: The frequency and magnitude of rain‐on‐snow floods have decreased across the western U.S., and snowmelt floods are occurring earlier Floods generated by convective storms (primarily in the Southwest) have increased in frequency and magnitude Except for the above‐mentioned changes, the frequency, magnitude, and timing of floods have been relatively stable over time